2010
DOI: 10.1111/j.1601-183x.2010.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of promoter IV‐driven BDNF transcription results in depression‐like behavior

Abstract: These results suggest that promoter IV-dependent BDNF expression plays a critical role in the control of moodrelated behaviors. This is the first study that directly addressed the effects of endogenous promoter-driven expression of BDNF in depression-like behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 55 publications
8
83
0
2
Order By: Relevance
“…Furthermore, a strong relationship exists between Bdnf and GABA (Yamada et al, 2002). It has recently been demonstrated that promoter IV-driven Bdnf transcription has a critical role in GABAergic transmission (Sakata et al, 2009), and mice with a selective deficiency of promoter-IV-dependent expression of Bdnf show depression-like behavior (Sakata et al, 2010). Collectively, these data support the potential link between Npas4, Bdnf, and GABA in contributing to the phenotypic changes observed in SERT À/À rats.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, a strong relationship exists between Bdnf and GABA (Yamada et al, 2002). It has recently been demonstrated that promoter IV-driven Bdnf transcription has a critical role in GABAergic transmission (Sakata et al, 2009), and mice with a selective deficiency of promoter-IV-dependent expression of Bdnf show depression-like behavior (Sakata et al, 2010). Collectively, these data support the potential link between Npas4, Bdnf, and GABA in contributing to the phenotypic changes observed in SERT À/À rats.…”
Section: Discussionsupporting
confidence: 68%
“…This led us to hypothesize that the transcription factor Npas4 may be altered in animal models of depression, and may eventually link alterations of neuroplastic markers, such as Bdnf, with an impaired function of the GABAergic system. On this basis, we investigated Npas4 expression in the hippocampus and prefrontal cortex of SERT + /À and SERT À/À rats, which model depression-and anxiety-related dysfunctions in humans, and we analyzed the expression of different GABAergic markers that may represent downstream targets of Npas4 and Bdnf signaling Sakata et al, 2010). Moreover, we investigated the ability of long-term treatment with the serotonin-norepinephrine reuptake inhibitor (SNRI) duloxetine to normalize molecular defects associated with genetic deletion of SERT.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired reversal learning as well as delayed initiation and deficits in response inhibition in the passive avoidance test (44) in BDNF-KIV mice are reminiscent of the slow adaption to rule changes and difficulty in inhibiting previously learned responses in patients with schizophrenia or PFC damage (45,46). Although spatial memory acquisition depends critically on the hippocampus, response learning in a taxon system also requires intact PFC function (21).…”
Section: Discussionmentioning
confidence: 99%
“…This structure allows for a very complex regulation of the Bdnf gene transcription in a time-, tissue-and stimulus-specific manner, which are all critical parameters for BDNF regulation of neuronal plasticity (Park and Poo, 2013). Notably, mice lacking promoter-4-driven Bdnf transcription show depression-like behaviors under stressful conditions (Sakata et al, 2010), suggesting a promoter-specific involvement of Bdnf in the response to stress.…”
Section: Florian Duclot and Mohamed Kabbaj*mentioning
confidence: 99%
“…This structure allows for a very complex regulation of the Bdnf gene transcription in a time-, tissue-and stimulus-specific manner, which are all critical parameters for BDNF regulation of neuronal plasticity (Park and Poo, 2013). Notably, mice lacking promoter-4-driven Bdnf transcription show depression-like behaviors under stressful conditions (Sakata et al, 2010), suggesting a promoter-specific involvement of Bdnf in the response to stress.In humans, however, numerous studies report reduced serum BDNF levels in depressed patients, which are then normalized to the levels of healthy controls by antidepressant treatment (BocchioChiavetto et al, 2006; Brunoni et al, 2008; Hoyer et al, 2012;Pallavi et al, 2013;Sen et al, 2008). However, serum BDNF levels do not systematically correlate with the severity of depressive symptoms, which questions its use as an accurate biomarker for depression (Molendijk et al, 2011;Molendijk et al, 2014).…”
mentioning
confidence: 99%